PENGARUH LITERASI KEUANGAN TERHADAP MINAT BERINVESTASI DI PASAR MODAL DENGAN PERKEMBANGAN TEKNOLOGI DIGITAL SEBAGAI VARIABEL MODERASI (Studi Empiris Mahasiswa Akuntansi Universitas Muhammadiyah Metro) - Rendi Fedias Saputra; Suyanto Suyanto; Ardiansyah Japlani (Jurnal Akuntansi AKTIVA, 2021)
This study aims to examine the effect of financial literacy on investment interest in the capital market with the development of digital technology as a moderating variable. This research uses a quantitative approach. This research used a quantitative approach. The population of this study was 292 students of Accounting Faculty of Economics and Business. The sampling technique was the purposive sampling method using certain criteria so as to obtain a sample of 113 respondents. Data analysis in this study used the SPSS (Statistical Packge Social Sciences) version 21 program with MRA (Moderated Regression Analysis) interaction testing. The results of this study indicated that financial literacy affects interest in investing in the capital market with the development of digital technology moderating the relationship between financial literacy and interest in investing in the capital market. Keywords: Financial Literacy, Interest in Investing, Digital Technology Development, Capital Market